ANALISIS BIAYA DAN MANFAAT EKONOMI PROYEK PENINGKATAN KELAS JALAN JALAN VETERAN â BRIGJEND. KATAMSO KOTA METRO, TAHUN 2011 - , Supriyadi, Drs. A. Budi Purnomo, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Costs and benefits Analysis is a practical technique that can be used to determine the relative merits of a project to be implemented. Its use can contribute to efficiency by ensuring that new projects are socially marginal costs exceed marginal social benefits are not considered for approval. If done well then the cost and benefit analysis can provide important information that will be used by the parties relating to the project in making decisions among alternative projects exist. This study aims to calculate and analyze the costs and benefits variable of economic of road investment projects of Improvement Classes Veteran - Brigjend. Katamso street of Metro City in 2011 so that can know the level of appropriateness criteria based on existing investments if the project is feasible or not (go or no go project). The data used in this study are primary and secondary data. Primary data obtained from direct observation in the field while the secondary data obtained from appropriate agencies such as Department of Transportation Metro City, Metro City Public Works Department, Bappeda City Metro and others. Analysis tools used in this study is the Benefit Cost Ratio (BCR), Net Present Value (NPV), Internal Rate Of Return (IRR) and Sensitivity Analysis. The results showed that at the end of economic life, the project will benefit a total of Rp41,404,248,725.72 and cost a total of Rp18,494,090,817.66, thus the net benefit obtained is Rp 22,910,157,908.05. By using the discount rate by 3.79 percent, 6.75 percent and 12.0 percent, obtained by the present value of these net benefits amounting to Rp11,922,092,266.80, Rp6,576,498,444.90 and Rp832,720,598.25